Analisis Struktur Railing Overhead Conveyor - Septiani Lestari; Mohamad Hakam; Mochammad Choirul Rizal (Proceedings Conference On Design Manufacture Engineering And Its Application, 2024)
The manual material handling process has several disadvantages, including a large workforce and a relatively long time, which hinders the continuity of the next process. So material handling tools are needed in the form of overhead conveyors to simplify the material handling process. This research aims to analyze the strength and feasibility of optimal construction according to company needs. Concentrate on railing and support construction. Requirements data based on company requests with a load capacity of 200kg, track length of 75 m. The final conclusion is that ASTM A36 material is used which has high safety for the overhead conveyor railing construction. The results of the analysis of the railing and support construction show that the von Mises stress value in the construction is 73,85 MPa with a deflection value of 9.08 mm. Meanwhile, for the supports, the von Mises stress results were 5,53MPa and the deflection value was 0,14 mm. The accumulated stresses and deflections that occur in each planned construction, both from manual calculations and simulations, are declared safe, because the stress and deflection values ??that occur in the construction are below the permitted stress and deflection values.